2017
DOI: 10.1111/acps.12730
|View full text |Cite
|
Sign up to set email alerts
|

The acute‐phase mediator serum amyloid A is associated with symptoms of depression and fatigue

Abstract: SAA might constitute a cross-diagnostic marker indicative of depressed mood and fatigue in a naturalistic patient setting. Because SAA activates Toll-like receptors 2 and 4, present on macrophages and glial cells, its association with depression severity could also implicate this inflammatory mediator in the pathogenesis of mood disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
(53 reference statements)
1
17
0
Order By: Relevance
“…Accordingly, activation of SNS by stress or different drugs could target immune cells (e.g., macrophages) that express all types of ARs. The present findings are in line with those of previous studies indicating the up-regulating effect of stress on SAA (Bryleva et al 2017; Collier et al 2011; Turlo et al 2015). They further support the involvement of different ARs in the stress-driven synthesis of both SAA1/2 and SAA3 in the liver, while total serum SAA protein load was also increased, indicating an AR-mediated systemic increase of these acute phase proteins.…”
Section: Discussionsupporting
confidence: 94%
“…Accordingly, activation of SNS by stress or different drugs could target immune cells (e.g., macrophages) that express all types of ARs. The present findings are in line with those of previous studies indicating the up-regulating effect of stress on SAA (Bryleva et al 2017; Collier et al 2011; Turlo et al 2015). They further support the involvement of different ARs in the stress-driven synthesis of both SAA1/2 and SAA3 in the liver, while total serum SAA protein load was also increased, indicating an AR-mediated systemic increase of these acute phase proteins.…”
Section: Discussionsupporting
confidence: 94%
“…Elevated levels of IL-10 are often reported in people with MDD [78][79][80]. Some researchers also observed that MDD severity is related to increased IL-10 [81,82].…”
Section: Il-10mentioning
confidence: 99%
“…In fact, it has been postulated that peripheral inflammation may not always result in either neuroinflammation or major depression. In unselected groups of depressed patients, levels of inflammatory biomarkers either do not correlate or correlate modestly with depression severity ( Cassidy-Bushrow et al, 2012 ; Bryleva et al, 2017 ; Jha et al, 2017b ; Köhler-Forsberg et al, 2017 ). Thus, identifying peripheral markers in blood that reflect neuroinflammation may help with developing novel treatments and could also identify specific subgroups that would require different treatments, thus personalizing the choice of currently available antidepressants.…”
Section: Introductionmentioning
confidence: 96%